2018
DOI: 10.1007/s13197-017-2999-4
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for separation and recovery of betaine from beet molasses based on cloud point extraction technique

Abstract: The aim of this work was to explore the possibility of the application of cloud point extraction (CPE) method in micelle media to recovery betaine from beet molasses. Response surface method was employed to assess the effects of surfactant concentration, molasses concentration, incubation time, pH, electrolyte concentration, mixing time, and surfactant type on efficiency of betaine recovery from beet molasses. Also, a mathematical model was developed to predict the effect of each variable and their interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 25 publications
(23 reference statements)
0
18
0
Order By: Relevance
“…Betaine, also known as trimethylglycine or glycine betaine, is a zwitterionic quaternary ammonium compound, which is one of the main byproducts during the process for sucrose extraction from sugar beets. 15,16 As a kind of zwitterionic quaternary ammonium compound, it can react with acids to form corresponding salts, such as betaine hydrochloride (BH). 17 Although BH has the advantages of nontoxicity, low cost and wide availability, application of BH in the chemical industry has been scarcely investigated and it is nowadays mostly used for animal feed.…”
Section: Introductionmentioning
confidence: 99%
“…Betaine, also known as trimethylglycine or glycine betaine, is a zwitterionic quaternary ammonium compound, which is one of the main byproducts during the process for sucrose extraction from sugar beets. 15,16 As a kind of zwitterionic quaternary ammonium compound, it can react with acids to form corresponding salts, such as betaine hydrochloride (BH). 17 Although BH has the advantages of nontoxicity, low cost and wide availability, application of BH in the chemical industry has been scarcely investigated and it is nowadays mostly used for animal feed.…”
Section: Introductionmentioning
confidence: 99%
“…However, the data showed that it is not required and the process can be operated without adjusting the pH in the range of 2–12 if these steps are carried out separately or not combined in one system. This is also consistent with the trend observed with the cloud point extraction method, where lower efficiencies were obtained with reducing or increasing the pH of the aqueous medium …”
Section: Resultsmentioning
confidence: 93%
“…This is also consistent with the trend observed with the cloud point extraction method, where lower efficiencies were obtained with reducing or increasing the pH of the aqueous medium. 25 For byproduct solutions, increasing initial pH reduced betaine extraction efficiency. The efficiency reduction was greater for molasses at higher pH values, suggesting that the extractant is hindered by or interacting with molasses constituents (having similar structure to betaine), which might be consumed or partially consumed during the fermentation of molasses.…”
Section: Effect Of Solution Ph and Mechanismmentioning
confidence: 99%
“…They recommended the CPE procedure driven by the low cost and ecofriendly technique which does not require any organic solvents. Mohammadzadeh et al (2018) recovered 80% betaine from beet molasses by using three steps CPE extraction technique under optimum conditions, such as 0.5% (w/v) surfactant concentration, 27.5% (w/v) of molasses concentration, 20 min of incubation time, at 6.1 pH, and 1.5% (w/v) of surfactant. The nature of betaine is hydrophobic, so it solubilized in surfactant and extraction was carried at pH 6.…”
Section: Bioactive Extraction From Food Processing Byproductsmentioning
confidence: 99%
“…They focused on developing a highly sensitive method for the determination of carbofuran, fenobucarb, arprocarb and isoprocarb. The alkaline hydrolysis of four carbamate pesticides reacted with 4-aminoantipyrene and Tx-114, Tx-100 Betaine recapture from beet molasses was attained up to 80% (Mohammadzadeh et al 2018) formed red colour products which were then enriched and were separated by CPE. The compounds present in coacervate phase were determined with HPLC system.…”
Section: Pesticide Residue Analysismentioning
confidence: 99%